Influence of the Economy Structure on Wages and Salaries in The EU Countries - Anna Szczepańska-Przekota (Communications of International Proceedings, 2022)
Wages and salaries determine the standard of living of a society. Society expects ever higher wages and salaries. Therefore, the question arises whether it is possible to restructure the economy in such a way that it will be able to meet these social expectations. This is the problem that this study focused on. 27 European Union countries for the years 2013-2020 were studied. A multi-level analysis was used to describe the relationship. The research showed that the systematic transformation of the economy towards modern branches in favor of the traditional ones caused an increase in wages and salaries. Another direction is state interference in the market. Higher government spending also fosters wages growth. However, the public should also know the negative sides of such a policy.
Keywords: Wages and salaries; Determinants; Economy structure; Multi-level analysis